Assessing the Potential Impacts of Contaminants on the Water Quality of Lake Victoria: Two Case Studies in Uganda - Nalumenya, Brian; Rubinato, Matteo; Jade, Catterson; Michael, Kennedy; Bakamwesiga, Hilary; Wabwire, Disan (Sustainability, 2024)
Nutrients are essential for the growth of aquatic life; however, in excess, they can result in a decline in water quality, posing serious risks to both human and aquatic organisms. Human activities, such as urbanisation, industry, and farming, can increase the amount of nutrients and other elements that reach receiving waterbodies like Lake Victoria in Uganda, which can be problematic at elevated levels. There is therefore a strong need to evaluate recent changes in pollutant concentrations and their potential negative effects. To contribute to this gap and to explore the pollutant changes in Lake Victoria, a series of water chemistry data (phosphate, nitrate, potassium, ammonium, sodium, sulphate, silica and chlorine) was collected between 2016 and 2023 in Uganda’s Napoleon Gulf (NG) and Murchison Bay (MB), primarily by the Ministry of Water and Environment (MWE). These locations were chosen based on their vicinity to expanding urban centres and agriculture, and they are also areas where fishing frequently occurs. The datasets were collected at different water depths (0.5–24 m). Data were analysed with the use of IBM’s Statistical Package for the Social Sciences (SPSS 28.0) software and confirmed the excessive concentrations of pollutants within MB compared to NG. The analysis identified the different nutrient types that exceeded internationally recognised thresholds relating to acceptable water quality during the data collection period. Seasonal variations were observed, during the dry season; nutrient levels, however, in NG showed higher nutrient concentrations during the wet season. The study’s capacity to inform local authorities and policymakers about such potential major sources of pollution is of crucial importance for beginning to address the potential impacts on human health and aquatic life.